Integrated Quantitative Business Network Planning: Towards a New Understanding of Supply Chain Management - Jahr, Michael (Journal of Advances in Management Sciences & Information Systems, 2015)
In business management quantitative modelling is a core competency. It enables structuring various complex problems; reduce systems to their relevant elements and to make objective and clear decisions. This especially applies to production-distribution networks which are formed by multiple independent and globally active companies. Here, individual goals and collective tasks meet so that experienced-based knowledge is no longer satisfactory. A literature review showed that there is no satisfactory concept available for superior network and quantitative operational management in multi-tier business networks. Therefore, in this article we focus quantitative supply chain models as starting point for stipulations among independent network partners. First, we deduce the main elements of quantitative modelling for inter- and intra-organisational production-distribution planning. Thereby, we present an extension of the Two-Stage-Production-Distribution-Problem which can be used as starting point for iterative supply chain coordination. Based on a literature review we introduce a novel pivotal point supply chain management model. The approach induces ongoing alignment of the strategic, tactic and operative tasks. On each level of this hierarchical planning frame specific plans are computed for comparison and adjustment. The advantages of this approach can be found in the reliable objective basis for negotiations and the repeatable combined inter- and intra-organisational management.